Aortic valve stenosis: Prognosis and therapy - Ristić-Anđelkov Anđelka; Gligić Branko; Damnjanović Milorad; Milovanović Jovanka; Matunović Radomir; Obradović Slobodan (Vojnosanitetski Pregled)
There is a long latent period in the clinical course of aortic valve stenosis in adults. Symptoms usually occur in the case of critical stenosis, when aortic orifice area is under 0.7cm2 (0.4 cm2/m2). In this study 78 patients with critical aortic valve stenosis were investigated. The first manifestation of the disease was dyspnea (78.2%), angina (52.5%), less often a syncope (34.6%), while 17.9% of patients were asymptomatic. Left ventricular systolic function was preserved in 77% of patients, while left ventricular dyastolic dysfunction occured in almost all the patients. In 42 patients (53.4%) aortic valve replacement was performed. Left ventricular systolic function improved in 88.1% of patients postoperativelly, as well as in patients with preoperativelly preserved or poor systolic function. Recovery was fast particularly during the first 6 postoperative months. After the surgery the improvement of the left ventricular dyastolic function was slower then systolic, particularly in patients with extreme hypertrophy of myocardium in whom the process of recovery might last several years.